1979
DOI: 10.1093/sf/57.3.871
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sex Role Differences on the Societal Reaction to Mental Retardation

Abstract: This paper investigates the thesis that sex role definitions in the U.S. support a double standard in societal reactions to mental incompetence. Role expectations for women are such that females are generally expected to be less competent than males in a variety of instrumental tasks, although perhaps more expressive. Males in turn are expected to be more active and aggressive than females in their exercise of the greater power and responsibility ascribed to them. In light of these generalized expectations we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1981
1981
1992
1992

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Perhaps the relationship represents a greater intolerance of mental impairment on the part of males than females. Other studies have reported that greater subnormality is perceived in male rather than female retardates who objectively behave quite similarly RETA RDA TION AND STIGMA 385 (Levinson, 1980) and that a greater degree of subnormal behavior may be tolerated for females than males before females are perceived, labeled, and treated as mentally retarded (Tudor et al, 1979;Churchill, 1964). It is possible that some of these differences will disappear as role expectations specific to gender become less pronounced.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Perhaps the relationship represents a greater intolerance of mental impairment on the part of males than females. Other studies have reported that greater subnormality is perceived in male rather than female retardates who objectively behave quite similarly RETA RDA TION AND STIGMA 385 (Levinson, 1980) and that a greater degree of subnormal behavior may be tolerated for females than males before females are perceived, labeled, and treated as mentally retarded (Tudor et al, 1979;Churchill, 1964). It is possible that some of these differences will disappear as role expectations specific to gender become less pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps there exists a double standard of societal reaction to mental and social impairments (Tudor et al, 1979), in which responses are more pronounced when the deviant is male. Even with the most severely impaired, cases in which Tudor et al indicated the effect was minimal, there was a finding in the predicted direction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations